The Evolution of Aggregative Multicellularity and Cell–Cell Communication in the Dictyostelia - Du, Qingyou; Kawabe, Yoshinori; Schilde, Christina; Chen, Zhi-hui; Schaap, Pauline (Journal of molecular biology, 2015)
Aggregative multicellularity, resulting in formation of a spore-bearing fruiting body, evolved at least six times independently amongst both eukaryotes and prokaryotes. Amongst eukaryotes, this form of multicellularity is mainly studied in the social amoeba Dictyostelium discoideum. In this review, we summarise trends in the evolution of cell-type specialisation and behavioural complexity in the four major groups of Dictyostelia. We describe the cell–cell communication systems that control the developmental programme of D. discoideum, highlighting the central role of cAMP in the regulation of cell movement and cell differentiation. Comparative genomic studies showed that the proteins involved in cAMP signalling are deeply conserved across Dictyostelia and their unicellular amoebozoan ancestors. Comparative functional analysis revealed that cAMP signalling in D. discoideum originated from a second messenger role in amoebozoan encystation. We highlight some molecular changes in cAMP signalling genes that were responsible for the novel roles of cAMP in multicellular development. [Display omitted] •Many eukaryotes and prokaryotes aggregate to form a community in which cells together construct a fruiting body.•Quorum sensing, two-component signalling and signalling mediated by the cyclic nucleotides cAMP and c-di-GMP play major roles in the social behaviour of prokaryotes.•Similar signalling mechanisms also regulate aggregation and cell-type specialisation during fruiting body formation in the eukaryote Dictyostelium discoideum.•Comparative genomic and gene functional analysis revealed that the cAMP and two-component signalling mechanisms that control Dictyostelium development originated from a stress response in the unicellular ancestors.